THE ARMED FORCES AND THE CURRENT MODEL OF SOCIAL RESPONSIBILITY - Ruiz-Rico Ruiz, Catalina (Journal of the Spanish Institute for Strategic Studies, 2018)
The Armed Forces are currently developing a model of social responsibility in the fields of human rights, the environment, equality and efficiency, among others. The leadership shown by the Armed Forces in the area of social responsibility stems from the adoption of sustainable measures and measures for modernization in connection with other institutions and administrations while respecting their own singularities. Social responsibility outreach takes place in foreign operations and in national operations with actions that go beyond mere compliance with legislation in force.